2016
DOI: 10.1007/s00441-016-2536-1
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine plus a high-fat diet triggers cardiomyocyte apoptosis

Abstract: Cigarette smoking is an important risk factor for diabetes, cardiovascular disease and non-alcoholic fatty liver disease. The health risk associated with smoking can be aggravated by obesity. Smoking might also trigger cardiomyocyte (CM) apoptosis. Given that CM apoptosis has been implicated as a potential mechanism in the development of cardiomyopathy and heart failure, we characterize the key signaling pathways in nicotine plus high-fat diet (HFD)-induced CM apoptosis. Adult C57BL6 male mice were fed a norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 67 publications
(114 reference statements)
4
22
0
Order By: Relevance
“…Cigarette smoke is a well-established risk factor for CVD and atherosclerosis[ 34 ]. The health care risk associated cigarette smoke for CVD is exaggerated by obesity or type II diabetic mellitus[ 6 , 19 , 20 ]. Nicotine has been suggested to participate in many of the adverse effects of smoke on the CV system[ 7 ], although there are also opposite reports that chronic nicotine treatment may have some beneficial vascular effects[ 35 ] We and others[ 3 , 36 ] have shown that chronic nicotine treatment promotes atherosclerotic lesion formation in apo E -/- mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarette smoke is a well-established risk factor for CVD and atherosclerosis[ 34 ]. The health care risk associated cigarette smoke for CVD is exaggerated by obesity or type II diabetic mellitus[ 6 , 19 , 20 ]. Nicotine has been suggested to participate in many of the adverse effects of smoke on the CV system[ 7 ], although there are also opposite reports that chronic nicotine treatment may have some beneficial vascular effects[ 35 ] We and others[ 3 , 36 ] have shown that chronic nicotine treatment promotes atherosclerotic lesion formation in apo E -/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated the importance of chemically stable compounds, present in the gas phase of cigarette smoke, in mediating endothelial injury and atherosclerosis[ 3 5 ]. Nicotine, one of the major active compounds of cigarette smoke, has been shown to have adverse effects upon the CV system[ 5 , 6 ], including autonomic imbalance, endothelial dysfunction and impaired coronary blood flow. It has been documented that nicotine, at concentration similar to that found in smokers’ blood, modifies lipid metabolism and impairs endothelial function in animals[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We carefully removed, dissected ventricles from 5 mice in each experimental group. Portions of left ventricles were either fixed in 2.5% glutaraldehyde for high-resolution light and electron microscopy or 4% formalin for terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labeling (TUNEL), and routine histological and immunohistochemical studies as described previously [24]. Five randomly selected left ventricular sections of~5 μm in thickness and taken 50 μm apart per animal in each group were viewed to obtain the rate of CM apoptosis or for immunohistochemical analyses and computerized densitometry.…”
Section: Mice and Tissue Preparationmentioning
confidence: 99%
“…Systemically, chronic exposure to nicotine has been associated with acute cardiac ischemic events, atherosclerosis, coronary artery disease, hypertension, and thrombosis . Nicotine exposure has also been reported to increase the malignant potential of pancreatic cancer stem cells and trigger the apoptosis of cardiomyocytes . Furthermore, nicotine impairs the function of polymorphonuclear leukocytes and causes hypercoagulation of blood as a result of increased platelet activation and raised fibrinogen levels (Figure ).…”
Section: Nicotine: Definition and Its Deleterious Effects On Oral Andmentioning
confidence: 99%